Complete mitochondrial genome sequences and the phylogenetic relationship of the endangered species Acoptolabrus leechi yooni (Deuve, 1990) (Coleoptera: Carabidae), Korea - Taeyeong Kwon; Eun Young Choi; Myeonghwan Kim; Jong Bong Choi; Myeong Cheol Kim; Hee Soo Lee; KyungHwan Moon; Young Ho Kim; Jong Kyun Park (Journal of Asia-Pacific Biodiversity, 2023)
Carabid beetles, are one of the largest taxonomic groups with >40,000 recorded species. Acoptolabrus leechi yooni has been listed as an endangered species in the Republic of Korea. The whole mitochondrial genome of A. leechi yooni consisted of a16,825-bp encompassing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and 1 control region. The DNA sequence comprises 79.4% of A-T region and 20.6% of G-C region. Phylogenetic analysis revealed that A. leechi yooni is very close to A. mirabilissimus mirabilissimus and A. changeonleei. This study provides a complete mitochondrial genome sequence of A. leechi yooni and basic data for protecting the endangered species.